The Self and Its Pleasures : Bataille, Lacan, and the History of the Decentered Subject - Dean, Carolyn J. (Carolyn Janice), 1960-; Project Muse. (Ithaca, N.Y. : Cornell University Press, 1992)
Why did France spawn the radical poststructuralist rejection of the humanist concept of 'man' as a rational, knowing subject? In this innovative cultural history, Carolyn J. Dean sheds light on the origins of poststructuralist thought, paying particular attention to the reinterpretation of the self by Jacques Lacan, Georges Bataille, and other French thinkers. Arguing that the widely shared belief that the boundaries between self and other had disappeared during the Great War helps explain the genesis of the new concept of the self, Dean examines an array of evidence from medical texts and literary works alike. The Self and Its Pleasures offers a pathbreaking understanding of the boundaries between theory and history.
Introduction -- Part one. Psychoanalysis and the self : introduction -- 1. The legal status of the irrational -- 2. Gender complexes -- 3. Sight unseen (reading the unconscious) -- Part two. Sade's selflessness : introduction -- 4. The virtue of crime -- 5. The pleasure of pain -- Part three. Headlessness : introduction -- 6. Writing and crime -- 7. Returning to the scene of the crime -- Conclusion.
Description based on print version record.
Keywords: Lacan, Jacques, -- 1901-1981.; Bataille, Georges, -- 1897-1962.; Bataille, Georges, -- 1897-1962.; Lacan, Jacques, -- 1901-1981.; Lacan, Jacques, -- 1901-1981.; Bataille, Georges, -- 1897-1962.; Bataille, Georges, -- 1897-1962.; Lacan, Jacques, -- 1901-1981.; Zelf; Poststructuralisme; Self (Philosophy); Self; Masochism; Intellectual life; Criminal psychology; LITERARY CRITICISM -- Semiotics & Theory; Psychologie criminelle -- Histoire; Masochisme -- Histoire; Moi (Philosophie) -- Histoire -- 20e siecle; Moi (Psychologie) -- Histoire -- 20e siecle; Criminal psychology -- History; Masochism -- History; Self (Philosophy) -- History -- 20th century; Self -- History -- 20th century; France; France -- Vie intellectuelle -- 20e siecle; France -- Intellectual life -- 20th century; History; Electronic books